2016
DOI: 10.1002/jcop.21793
|View full text |Cite
|
Sign up to set email alerts
|

School Inclusion: A Multidimensional Framework and Links With Outcomes Among Urban Youth With Disabilities

Abstract: As schools move toward inclusion of students with disabilities, there is need for a common framework for school inclusion, as well as assessment of inclusion in relation to student educational experiences. We propose an ecological framework that suggests school inclusion is best examined as a multidimensional construct with subtypes of inclusive best practices (organizational, academic, assessment and planning, and social). This study examines the extent to which schools (N = 11) are practicing each type of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The most important question is whether there are real participation and achievement opportunities for all learners that would rule out any form of exclusion from education. Inclusion is a multidimensional process, which involves organizational, academic, assessment and planning as well as social aspects (McMahon et al, 2016). Children can be included academically and socially.…”
Section: Inclusion Of a Child With A Hearing Impairment In A Mainstrementioning
confidence: 99%
“…The most important question is whether there are real participation and achievement opportunities for all learners that would rule out any form of exclusion from education. Inclusion is a multidimensional process, which involves organizational, academic, assessment and planning as well as social aspects (McMahon et al, 2016). Children can be included academically and socially.…”
Section: Inclusion Of a Child With A Hearing Impairment In A Mainstrementioning
confidence: 99%
“…Wiener and Tardiff (2004) in a Canadian study found that on a wide variety of social outcomes (which included measures of friendship, loneliness, self-perceptions and social skills), comparisons between students educated in inclusive versus non-inclusive settings favored the more inclusive approach. McMahon, Keys, Berardi, Crouch and Coker (2016) examined the degree to which schools serving a high percentage of African-American and Latino-American students were supporting the social aspects of IE and the links between teacher-reported inclusion practices and student-and school-reported social outcomes. Findings supported the benefits of IE practices, in that students in schools effectively implementing this approach through ensuring that all extracurricular activities were accessible experienced greater social opportunities, participated more frequently in school activities and experienced a greater sense of school belonging.…”
Section: Social and Psychological Outcomesmentioning
confidence: 99%
“…§ 1400 2004) and its predecessors call for students to receive appropriate supports in the least restrictive environment and to participate with nondisabled peers to the maximum extent appropriate. School inclusion is associated with school belonging, school satisfaction, and academic achievement, yet schools report variation in implementation of best practices (McMahon, Keys, Berardi, Crouch, & Coker, 2016). School inclusion policies are often lacking because inclusion requires improvements and alterations in teaching instruction and improved organizational capacity of school staff (Sautner, 2008).…”
Section: Discussionmentioning
confidence: 99%